Etos Kerja Islami dalam Perspektif Hadis Nabi: Panduan untuk Kehidupan Modern - Ansharullah (POROS ONIM: Jurnal Sosial Keagamaan, 2024)
Islamic work ethic plays an important role in shaping the behaviour of Muslims in facing modern challenges. The culture of laziness and low productivity has also become a significant issue among the people. This study aims to analyse the motivation to work based on the Prophet Muhammad's hadith with a tahlili approach. The results show that working hard is not only to fulfil material needs, but also has the value of worship if done sincerely, even though the results are small. The 21 sahih transmission routes listed in Kutub al-Tis'ah were analysed to ensure the validity of the hadith. The study highlights the importance of Islamic work ethic as a solution to address social problems such as unemployment and low productivity in society. As a recommendation, the study encourages the integration of Islamic work ethic values in education and job training programmes to enhance social resilience and build a productive workforce in Muslim communities.